Numerical Simulation of Melt Filtration Process - Bruna, Marek; Bolibruchova, Dana; Prochazka, Petr (Communications - Scientific Letters of the University of Zilina, 2016)
The paper aims to comprehensively elaborate the impact of ceramic filter design on filling parameters during the casting of aluminium alloys. Experimental work focuses mainly on the evaluation of velocity, filling time and turbulences in the close vicinity of the filter by numerical simulation. The whole experiment was divided into two stages: in the first stage was evaluated set of three filters with different channels cross-section geometry, and in the second stage was evaluated set composed of four filters with different number of channels and channels diameter.
Keywords: filtration; numerical simulation; aluminium alloys